(untitled) (Revista Electrónica REDINE, 2025)
In recent decades, advertising communication has undergone changes in its creative language to align with the promotion of goods and services through messages of social inclusion and respect for human rights. It is uncommon for well-known brands to exercise creative freedom in a striking manner, saturated with critical meaning; however, over the past decade, there has been a surge in marketing strategies aimed at increasing sales or turning these brands into trends by using inclusive communication to challenge social conventions laden with prejudices and stereotypes. That is why the purpose of this research was to interpret the perspectives of advertising and communication specialists regarding the potential challenges of inclusive advertising for the Venezuelan creative industry. This is a qualitative study, based on the interpretative paradigm, using the hermeneutic phenomenological method and semi-structured interviews. Among the findings derived from the assessment of advertising, stereotypes, and the lag in the Venezuelan creative industry are that there is a delay in adopting inclusive trends due to the severe economic, political, and cultural crisis affecting the country, where addressing urgent needs takes priority. Additionally, there is a lack of ’reimagining’ the commercial purpose of advertising to include equality and equity, regardless of gender